Analysis of the Development of the Paroxysmal Eruption of the Sheveluch Volcano on April 10–13, 2023, Based on Data from Various Satellite Systems - Girina O.A.; Loupian E.A.; Horváth Á; Melnikov D.V.; Manevich A.G.; Nuzhdaev A.A.; Bril A.A.; Ozerov A.Yu.; Kramareva L.S.; Sorokin A.A. (Springer, 2023)
The Sheveluch volcano is the most active volcano in Kamchatka. The paroxysmal explosive eruption of the volcano that destroyed the lava dome in the volcanic crater continued on April 10–13, 2023. According to various satellite data, the height of the separate eruptive clouds probably exceeded 15 km above sea level. A powerful cyclone, which dominated the entire Kamchatka Peninsula, pulled the eruptive cloud to the west, turned it to the south, stretched it to the north, and directed it to the east from the volcano. The dynamics of the development of ash and aerosol clouds of this eruption is reflected in the animations made from a series of Himawari-9 satellite images in the VolSatView IS from 08:00 UTC on April 10 to 07:00 UTC on April 14 (http://d33.infospace.ru/jr_d33/materials/2023v20n2/283-291/1683110898.webm) and of the Arctica-M1 satellite from 16:00 to 21:30 UTC on April 10 (http://d33.infospace.ru/jr_d33/materials/2023v20n2/283-291/1683821166.webm). It was noted that the eruptive column was not vertical: for example, at the initial moment of the eruption on April 10 at 13:20 UTC, it deviated to the north–northeast; on April 11, at 12:00 UTC to the northwest; and, on April 12, at 7:00 UTC to the southwest. During the paroxysmal eruption, sulfur dioxide continuously entered the atmosphere, the maximum amount of which was released on April 10–11, as a result of the explosive destruction of the lava dome of the Sheveluch volcano. Ash clouds along with aerosol clouds on April 10–13 were stretched into a strip more than 3500 km long from west to northeast. On April 21–22, the Sheveluch aerosol cloud was observed in the region of the Scandinavian Peninsula. The total area of the territory of Kamchatka and the Pacific Ocean where ash and aerosol plumes and clouds were observed during the April 10–13 eruption was about 3280000 km2. The paroxysmal eruption of Sheveluch volcano belongs to the sub-Plinian type because it is characterized by a large height of the eruptive cloud and a long event duration. For this eruption, the Volcanic Explosivity Index is estimated to be 3–4. A detailed description of the paroxysmal explosive eruption of the Sheveluch volcano and the spread of the eruptive cloud was performed based on data from various satellite systems (Himawari-9, NOAA-18/19, GOES-18, Terra, Aqua, JPSS-1, Suomi NPP, Arctica-M1, etc.) in the information system “Remote Monitoring of Kamchatka and Kuril Islands Volcanic Activity” (VolSatView, http://kamchatka.volcanoes.smislab.ru).
Keywords: 38.37.25 Вулканология; Шивелуч